Age-specific disparity in insomnia among COVID-19 patients in Fangcang shelter hospitals: a population-based study in Shanghai, China - Shi, Ruizi; Wang, Yihui; Chen, Ying; Yang, Zhitao; Jing, Feng; Shang, Hanbing; Chen, Erzhen; Zhou, Ying (Frontiers in Neurology, 2024)
Background: Fangcang shelter hospital is a quarantine facility with primary medical treatment capabilities for mild and asymptomatic SARS-CoV-2 cases. Little is known about the age-specific prevalence of insomnia among patients in Fangcang shelter hospital, particularly in older age groups. Methods: This cross-sectional study was conducted in the three largest Fangcang shelter hospitals during the lockdown period from March to May 2022 in Shanghai. The patients’ demographic and medical information was recorded. Insomnia was defined according to the prescriptions for zolpidem and estazolam. The overall and age-specific prevalence and risk factors of insomnia were investigated by regression models. Results: There were 239448 patients in this study (59.09% male, median age 42, 73.41% asymptomatic), with the prevalence of insomnia being 3.1%. The prevalence of insomnia was distinct across age groups (<18 years: 0.23%, 18-64 years: 2.64%, and ≥65 years: 10.36%). SARS-CoV-2 vaccine, regardless of doses, significantly associated with decreased risk of insomnia for the group aged ≥65 years. Three doses of the vaccine reduced the risk of insomnia for patients aged 18-64 years. An extra day in the hospital significantly increased the risk of insomnia by about 10% for all age groups. Mild symptoms were significantly associated with a higher risk of insomnia among persons aged <65 years-old, while being male and residing in the surrounding area were negatively associated with insomnia for all adults. Conclusion: The older people were high-risk population of insomnia in Fangcang shelter hospital. SARS-CoV-2 vaccination might decrease the risk of insomnia for adults, especially elderly, which indicated the benefits of vaccination on insomnia among infected patients.